Optimalisasi Peran Bhabinkamtibmas dalam Upaya Peningkatan Pencegahan Kejahatan Berbasis Masyarakat Terkait Kejahatan Terorisme - Alief Maulana; Anggi Aulina Harahap (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
Terrorism is a type of crime that cannot be classified as an ordinary crime. The threat of terrorism is not only a problem for a particular country or region, but a global threat. The police as part of law enforcement agencies, are responsible for maintaining security, order, providing comfort, and protection to the community in accordance with Law (UU) Number 2 of 2002 concerning the Indonesian National Police through community policing. This research uses qualitative research methods, observation techniques and library studies. In addition to observation which is the primary data collection technique, researchers also use secondary data collection techniques using library studies. The role of Bhabinkamtibmas in preventing terrorism through the Community Policing approach makes the right contribution. By building a close and trusting relationship with the community, Bhabinkamtibmas creates an environment where people feel comfortable to report suspicious activities and actively participate in prevention efforts.